PENINGKATAN KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR MENGGUNAKAN MEDIA GAMBAR - Darnis Arif (Pedagogi: Jurnal Ilmu Pendidikan, 2014)
Speaking skill is one of language skills wich has an important role in life. By means os speaking skill, someone could communicate to give information, give knowledge to others. The background of this research is the low rate of speaking skill of the fourth grade students of Elementary School number 8 Padang Besi Padang. It’s because the learning of speaking skill did not get an equal portion compared to other skills such as reading and writing. Beside of that, the learning of speaking skill did not use a media wich could stimulate students imagination to arrange and deliver their ideas orally. This Class Action Research is done in two cycles. Every cycle consist of speaking teaching plan, proses of teaching speaking, and teaching speaking’s evaluation. The finding of the research shows that picture media can improve the speaking skill of the fourth grade students in Elementary School number 8 Padang Besi Padang. So, it is suggested to use picture media in teaching speaking.